Pengaruh Penggunaan Model Pembelajaran Discovery Learning Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Informatika Kelas X SMA Negeri 14 Maros - Nur Isma; Aisyah Aisyah; Sadriana Ayu; Nasir Nasir; Muhammad Wahyu (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The discovery learning model is a learning model that can directly involve students into learning activities through an argument, students can argue, discuss, and can read for themselves and try themselves, so that students can do learning independently. This study aims to determine the effectiveness of the DL (Discovery Learning) type cooperative learning model by applying it to informatics learning in class X.2 and X.4 SMA Negeri 14 Maros is expected to achieve the objectives to be achieved. This research method is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of four meetings, the first part as cycle 1 and 4 meetings the second part as cycle 2 and 4 meetings. The research subjects consisted of class X.2 students totaling 36 people and class X.4 students totaling 35 people. The collection techniques were documentation, observation, and tests. The results of this study can be concluded that in its application in the learning process of the Discovery Learning learning model, students are very good at responding to the material presented, it's just that some students when in the learning process there are students who sleep and do not focus on receiving material and also telling stories with their friends. And also student learning outcomes on informatics learning improved better from the aspects of attitude competence, knowledge competence and skill competence. Therefore, it can be concluded that by applying the Discovery Learning learning model, students are very creative in the learning process.